Polyoxometallate intercalation MXene material as well as preparation method and application thereof
By forming a polydopamine coating on the MXene material and inserting polyoxygenate, the problems of easy oxidation of MXene and easy dissolution of polyoxygenate are solved, catalytic performance and stability are improved, and efficient removal of antibiotics is achieved. Meets practical application needs.
Patent Information
- Application Number
- CN202411393022.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to effectively degrade antibiotic contamination, especially because MXene materials are easily oxidized during the synthesis process and polyoxygenates are easily dissolved, resulting in a degradation of catalytic performance and low purification efficiency.
Dopamine is self-polymerized under weak alkaline conditions to form a polydopamine (PDA) coating to protect MXene and insert polyoxygenate (SiW9Co3) to form MXene-SiW9Co3@PDA composite material, improve its stability and layer spacing, and reduce The dissolution of polyoxygenates enhances the removal of antibiotics.
It realizes a high-activity and strong stability MXene-based polyoxygenate composite material, which can efficiently remove a variety of antibiotics from water, has the advantages of wide applicability and simple operation, and meets practical application needs.
Smart Images

Figure CN119259089A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of antibiotic degradation, and in particular to a polyoxometalate intercalated MXene material and a preparation method and application thereof. Background Art
[0002] With the rapid development of industrialization, antibiotics have been widely used in medicine, poultry, aquaculture and other fields. Many antibiotics have been detected in groundwater, surface water, sediments and even drinking water, posing potential risks to water supply and ecosystems. In view of the potential toxicity and low biodegradability of antibiotics, they are considered to be important emerging pollutants. Due to their strong hydrophilicity, high stability and antibacterial properties, antibiotics are difficult to be effectively eliminated by conventional treatment processes. Therefore, the development of efficient and environmentally friendly degradation technology has become one of the current research hotspots.
[0003] In recent years, conventional treatment technologies such as membrane filtration, physical adsorption and biodegradation have been widely studied in water treatment, but these technologies generally have disadvantages such as high energy consumption, poor mineralization capacity, high cost and low purification efficiency. Advanced oxidation technology (AOPs) is widely used to remove organic pollutants in wastewater because of its high efficiency and easy operation. Peroxymonosulfate (PMS) technology, as a type of AOPs, has the advantages of convenient transportation and storage and good stability. It can be activated by heating, ultraviolet (UV), ultrasound, transition metal-based catalysts, electrochemistry and other methods. Transition metals are widely used because of their high catalytic activity, among which Co 2+ It is considered to be the most effective ion for activating PMS.
[0004] At present, the research on two-dimensional transition metal carbides / nitrides (MXene) has grown exponentially due to its advantages such as diverse varieties, unique layered structures, excellent electrical conductivity, hydrophilicity, thermal conductivity, in-situ initiation, strong storage capacity and large specific surface area. In addition, the functional groups (-F, -O, -OH) on the surface of MXene make it have good hydrophilicity and chemical activity, and can be composited with other functional materials. However, it is easy to oxidize during the synthesis process, and too many surface functional groups make it difficult to form a close interface contact, which limits the application of constructing efficient catalysts in semiconductor coupling. Due to the lack of surface protection, MXene is easily oxidized in the air, causing the catalytic performance to decrease and deactivate. Therefore, the long-term stability of MXene-based catalysts still needs to be improved. Dopamine (DA) can self-polymerize to form polydopamine (PDA) under weak alkaline conditions because it contains a large number of amine and catechol functional groups and has the ability to adhere to the surfaces of various materials. PDA coating can be formed on various substrates. More importantly, PDA has strong reducing properties, which can prevent the encapsulated material from being oxidized. At the same time, PDA can also serve as a medium for redox reactions and show high affinity for metal ions without weakening the performance of MXene.
[0005] Polyoxometalates (POMs) are a type of nanoclusters with an ordered structure formed by multiple metal oxide octahedra connected by oxygen atoms. They have the advantages of thermodynamic stability, chemical stability, multi-electron redox ability, size controllability and structural precision. They are widely used in various fields such as energy storage, catalysis, and sensors. However, POMs are easily soluble in water and other organic solvents. When synthesizing POMs composite materials, polyoxometalates are difficult to load; at the same time, POMs are difficult to form a dense structure with the material, resulting in a large amount of dissolution. MXene and POMs have complementary properties and dimensions, which can produce synergistic effects. For example, 2D MXene can provide an electron conduction matrix, while POMs can provide a columnar effect. The two can form a supporting structure and promote ion transport, thereby efficiently activating PMS. Therefore, it is of great significance to obtain a polyoxometalate intercalated MXene material that efficiently catalyzes antibiotics and its preparation method. Summary of the invention
[0006] The purpose of the present invention is to provide a polyoxometalate intercalated MXene material and a preparation method and application thereof in order to overcome the deficiencies of the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a polyoxometalate intercalated MXene material, comprising the following steps:
[0009] 1) Sodium tungstate, sodium silicate and water are mixed, the mixed solution is reacted with hydrochloric acid and then filtered to obtain a filtrate;
[0010] 2) reacting the filtrate with a sodium carbonate solution to obtain a precipitate, and drying the precipitate to obtain SiW9;
[0011] 3) reacting the cobalt acetate solution and the SiW9 solution, filtering the solution, mixing the filtrate with potassium chloride and drying the mixture to obtain SiW9Co3;
[0012] 4) performing a first reaction on lithium fluoride and hydrochloric acid, and performing a second reaction on the first reaction product and titanium aluminum carbide to obtain a MXene dispersion;
[0013] 5) Mixing the MXene dispersion, dopamine hydrochloride and SiW9Co3, adjusting the pH value of the mixture and reacting to obtain a polyoxometalate intercalated MXene material.
[0014] Preferably, in the mixed solution of step 1), the concentration of sodium tungstate is 2.5-3 mol / L, and the concentration of sodium silicate is 0.4-0.5 mol / L; the volume ratio of the mixed solution to hydrochloric acid is 19-21:12-14, and the concentration of hydrochloric acid is 5.5-6.5 mol / L;
[0015] The reaction temperature is 70-95° C., and the reaction time is 0.5-3 h.
[0016] Preferably, in step 2), the volume ratio of the filtrate to the sodium carbonate solution is 1.5-2.5:1, and the concentration of the sodium carbonate solution is 2.9-3.4 mol / L;
[0017] The reaction temperature is 20-40° C., and the reaction time is 5-30 min; the drying temperature is 50-80° C., and the drying time is 8-12 h.
[0018] Preferably, in step 3), the concentration of the cobalt acetate solution is 78-82 mol / L, the concentration of the SiW9 solution is 38-43 mmol / L, and the volume ratio of the cobalt acetate solution to the SiW9 solution is 2.5-3.5:1.5-2.5;
[0019] Step 3) The reaction temperature is 60-90°C and the reaction time is 0.5-3h;
[0020] The concentration of potassium chloride in the mixed solution obtained by mixing the filtrate and potassium chloride is 134.14~
[0021] 402.42mmol / L, mixing time is 10 to 30min.
[0022] Preferably, in step 4), the mass volume ratio of lithium fluoride to hydrochloric acid is 0.8-3.6 g:10-40 mL, and the concentration of hydrochloric acid is 6-12 mol / L; the mass ratio of lithium fluoride to titanium aluminum carbide is 0.8-3.6:0.5-2.
[0023] Preferably, the concentration of the MXene dispersion is 0.5 to 2 mg / L; the temperatures of the first reaction and the second reaction are independently 30 to 45° C., the time of the first reaction is 5 to 20 min, and the time of the second reaction is 24 to 60 h.
[0024] Preferably, in step 5), the volume mass ratio of the MXene dispersion, dopamine hydrochloride and SiW9Co3 is 50-200 mL: 50-200 mg: 5-240 mg; the pH value of the mixed solution is adjusted to 8-9; the reaction temperature is 15-30°C, and the reaction time is 8-30 h.
[0025] The present invention also provides a polyoxometalate intercalated MXene material prepared by the preparation method.
[0026] The present invention also provides an application of the polyoxometalate intercalated MXene material in the degradation of antibiotics, wherein the polyoxometalate intercalated MXene material and an antibiotic solution are mixed, and the mixed solution is subjected to a degradation reaction with peroxymonosulfate.
[0027] Preferably, the mass volume ratio of the polyoxometalate intercalated MXene material, the antibiotic solution and the peroxymonosulfate is 10-50 mg: 100 mL: 10-100 mg;
[0028] The concentration of the antibiotic solution is 10-40 mg / L, and the antibiotic is sulfamethoxazole, norfloxacin, tetracycline hydrochloride or amoxicillin;
[0029] The mixing temperature is 15-40° C., and the mixing time is 10-40 min; the degradation reaction temperature is 15-40° C., and the degradation reaction time is 5-35 min.
[0030] The beneficial effects of the present invention include the following:
[0031] 1) The present invention aims at the key problems of easy oxidation of MXene and easy dissolution of polyoxometalates in the preparation process of polyoxometalates and MXene composite materials. The method of self-polymerization of dopamine under weak base is used to form polydopamine on MXene, which not only protects MXene but also reduces the dissolution of polyoxometalates. First, SiW9Co3 and MXene are prepared by hydrothermal method and in-situ hydrofluoric acid method respectively, and then SiW9Co3 is inserted into the MXene interlayer by a one-step method, which increases the interlayer spacing of MXene and reduces the dissolution of polyoxometalates. A simple and mild method is used to prepare a few-layer MXene-based polyoxometalate composite material MXene-SiW9Co3@PDA with high activity, stability and strong antioxidant properties.
[0032] 2) The method for preparing the MXene-SiW9Co3@PDA composite material of the present invention is simple and the conditions are mild; polyoxometalates can enter the interlayer of MXene, expand the interlayer distance of MXene while reducing the dissolution of polyoxometalates, and the introduction of polydopamine prevents oxidation of the composite material and improves the stability of the composite material; at the same time, the composite material can achieve efficient removal of a variety of antibiotics in water, has the advantages of a wide range of applications, simple operation, high removal rate, etc., and can meet the needs of practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The SEM and TEM images of the MXene dispersion prepared in Example 1;
[0034] Figure 2 The SEM and TEM images of the MXene-SiW9Co3@PDA composite material prepared in Example 1;
[0035] Figure 3 TEM images of the MXene interlayer spacing in the MXene dispersion and MXene-SiW9Co3@PDA composite material prepared in Example 1, wherein a is a TEM image (10 nm) and b is a TEM image (50 nm);
[0036] Figure 4 The degradation effects of the MXene-SiW9Co3@PDA composite material of Example 1 on sulfamethoxazole, norfloxacin, amoxicillin and tetracycline hydrochloride respectively. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing a polyoxometalate intercalated MXene material, comprising the following steps:
[0038] 1) Sodium tungstate, sodium silicate and water are mixed, the mixed solution is reacted with hydrochloric acid and then filtered to obtain a filtrate;
[0039] 2) reacting the filtrate with a sodium carbonate solution to obtain a precipitate, and drying the precipitate to obtain SiW9;
[0040] 3) reacting the cobalt acetate solution and the SiW9 solution, filtering the solution, mixing the filtrate with potassium chloride and drying the mixture to obtain SiW9Co3;
[0041] 4) performing a first reaction on lithium fluoride and hydrochloric acid, and performing a second reaction on the first reaction product and titanium aluminum carbide to obtain a MXene dispersion;
[0042] 5) Mixing the MXene dispersion, dopamine hydrochloride and SiW9Co3, adjusting the pH value of the mixture and reacting to obtain a polyoxometalate intercalated MXene material.
[0043] In the mixed solution of step 1) of the present invention, the concentration of sodium tungstate is preferably 2.5-3 mol / L, more preferably 2.7-2.8 mol / L, and more preferably 2.75 mol / L; the concentration of sodium silicate is preferably 0.4-0.5 mol / L, more preferably 0.43-0.47 mol / L, and more preferably 0.4506-0.46 mol / L; the volume ratio of the mixed solution to hydrochloric acid is preferably 19-21:12-14, more preferably 19.5-20.5:12.5-13.5, and more preferably 20:13; the concentration of hydrochloric acid is preferably 5.5-6.5 mol / L, more preferably 5.8-6.2 mol / L, and more preferably 6 mol / L;
[0044] The reaction temperature is preferably 70 to 95° C., more preferably 75 to 90° C., more preferably 80 to 85° C., and the reaction time is preferably 0.5 to 3 h, more preferably 1 to 2.5 h, more preferably 1.5 to 2 h.
[0045] In the present invention, the volume ratio of the filtrate to the sodium carbonate solution in step 2) is preferably 1.5 to 2.5:1, more preferably 1.8 to 2.2:1, and more preferably 2:1; the concentration of the sodium carbonate solution is preferably 2.9 to 3.4 mol / L, more preferably 3.1 to 3.2 mol / L, and more preferably 3.15 mol / L;
[0046] The reaction temperature is preferably 20-40°C, more preferably 25-35°C, more preferably 30°C; the reaction time is preferably 5-30 min, more preferably 10-25 min, more preferably 15-20 min; the drying temperature is preferably 50-80°C, more preferably 55-75°C, more preferably 60-70°C; the drying time is preferably 8-12 h, more preferably 9-11 h, more preferably 10 h.
[0047] In the present invention, the concentration of the cobalt acetate solution in step 3) is preferably 78-82 mol / L, more preferably 79-81 mol / L, and more preferably 80.03-80.5 mol / L; the concentration of the SiW9 solution is preferably 38-43 mmol / L, more preferably 39-41 mmol / L, and more preferably 40-40.14 mmol / L; the volume ratio of the cobalt acetate solution to the SiW9 solution is preferably 2.5-3.5:1.5-2.5, more preferably 2.8-3.2:1.8-2.2, and more preferably 3:2; the solvents of the cobalt acetate solution and the SiW9 solution are preferably water.
[0048] In the present invention, the reaction temperature in step 3) is preferably 60 to 90°C, more preferably 65 to 85°C, more preferably 70 to 80°C, and the reaction time is preferably 0.5 to 3h, more preferably 1 to 2.5h, more preferably 1.5 to 2h;
[0049] In the mixed solution obtained by mixing the filtrate and potassium chloride, the concentration of potassium chloride is preferably 134.14-402.42 mmol / L, more preferably 200-350 mmol / L, more preferably 268.5-300 mmol / L; the mixing time is preferably 10-30 min, more preferably 15-25 min, more preferably 20 min.
[0050] In the present invention, the solution obtained by the reaction in step 3) is cooled and filtered, and the cooling temperature is preferably 20-40°C, more preferably 25-35°C, and more preferably 30°C; the mixed solution obtained by mixing the filtrate and potassium chloride is filtered, the precipitate is dried, and ground in sequence to obtain SiW9Co3; the drying temperature is preferably 50-80°C, more preferably 55-75°C, and more preferably 60-70°C; the drying time is preferably 8-12h, more preferably 9-11h, and more preferably 10h.
[0051] In the present invention, the mass volume ratio of lithium fluoride and hydrochloric acid in step 4) is preferably 0.8-3.6 g: 10-40 mL, further preferably 1.2-3 g: 15-35 mL, and more preferably 1.6-2.5 g: 20-30 mL; the concentration of hydrochloric acid is preferably 6-12 mol / L, further preferably 8-10 mol / L, and more preferably 9 mol / L; the mass ratio of lithium fluoride and titanium aluminum carbide (Ti3AlC2) is preferably 0.8-3.6: 0.5-2, further preferably 1.5-3: 1-1.5, and more preferably 2-2.5: 1.2-1.3.
[0052] In the present invention, the concentration of the MXene dispersion is preferably 0.5 to 2 mg / L, more preferably 1 to 1.5 mg / L; the temperatures of the first reaction and the second reaction are independently preferably 30 to 45°C, more preferably 35 to 40°C, the time of the first reaction is preferably 5 to 20 min, more preferably 10 to 15 min, and the time of the second reaction is preferably 24 to 60 h, more preferably 35 to 50 h, and more preferably 40 to 48 h.
[0053] In the present invention, the reaction solution obtained by the second reaction in step 4) is sequentially subjected to centrifugal washing, ultrasonication, and centrifugation to obtain an upper layer of MXene dispersion, the rotation speed of the centrifugal washing is preferably 3000-6000 r / min, more preferably 3500-5500 r / min, and more preferably 4000-5000 r / min, the reagents for centrifugal washing are preferably hydrochloric acid and water in sequence, the number of hydrochloric acid washings is preferably 1-5 times, more preferably 2-4 times, the concentration of hydrochloric acid is preferably 1-3 mol / L, more preferably 2 mol / L, and the water is washed until the pH value of the upper liquid is ≥6 or the upper liquid turns black; The temperature of ultrasound is preferably 5-30°C, more preferably 10-25°C, and more preferably 15-20°C; the power of ultrasound is preferably 150-200W, more preferably 160-190W, and more preferably 170-180W; the time of ultrasound is preferably 0.5-2h, and more preferably 1-1.5h; the speed of centrifugation is preferably 3000-5000r / min, more preferably 3500-4500r / min, and more preferably 4000r / min; the time of centrifugation is preferably 5-30min, more preferably 10-25min, and more preferably 15-20min.
[0054] In the present invention, the MXene dispersion liquid and dopamine hydrochloride (C8H 11 The volume mass ratio of NO2·HCl) and SiW9Co3 is preferably 50-200mL:50-200mg:5-240mg, more preferably 80-160mL:80-160mg:50-200mg, more preferably 100-130mL:100-130mg:80-110mg; the pH value of the mixed solution is preferably adjusted to 8-9, more preferably 8.5, and the reagent for adjusting the pH value is preferably tris(hydroxymethyl)aminomethane (C4H 11 NO3); the reaction temperature is preferably 15 to 30°C, more preferably 20 to 25°C, the reaction time is preferably 8 to 30h, more preferably 12 to 26h, more preferably 20 to 24h.
[0055] In the present invention, the reaction solution obtained by the reaction in step 5) is centrifugally cleaned, precipitated and dried, and ground in sequence to obtain a polyoxometalate intercalated MXene material; the reagent for centrifugal cleaning is preferably water, and the speed of centrifugal cleaning is preferably 5000-8000r / min, more preferably 5500-7500r / min, and more preferably 6000-7000r / min; the number of centrifugal cleanings is preferably 1-4 times, more preferably 2-3 times, and the drying temperature is preferably 40-80°C, more preferably 50-70°C, and more preferably 60°C; the drying time is preferably 8-12h, more preferably 9-11h, and more preferably 10h.
[0056] In the present invention, during the reactions in steps 1), 2), 3), 5), and the first reaction and the second reaction in step 4), the stirring rate is independently preferably 200 to 500 r / min, and more preferably 300 to 400 r / min.
[0057] The present invention also provides a polyoxometalate intercalated MXene material (MXene-SiW9Co3@PDA composite material) prepared by the preparation method.
[0058] The present invention also provides an application of the polyoxometalate intercalated MXene material in the degradation of antibiotics, wherein the polyoxometalate intercalated MXene material and an antibiotic solution are mixed, and the mixed solution is subjected to a degradation reaction with peroxymonosulfate (PMS).
[0059] In the present invention, the mass volume ratio of the polyoxometalate intercalated MXene material, the antibiotic solution and the peroxymonosulfate is preferably 10-50 mg: 100 mL: 10-100 mg, more preferably 20-40 mg: 100 mL: 30-80 mg, and more preferably 20-30 mg: 100 mL: 50-60 mg;
[0060] The concentration of the antibiotic solution is preferably 10 to 40 mg / L, more preferably 20 to 30 mg / L; the antibiotic is preferably sulfamethoxazole, norfloxacin, tetracycline hydrochloride or amoxicillin;
[0061] The mixing temperature is preferably 15-40°C, more preferably 20-35°C, more preferably 25-30°C, and the mixing time is preferably 10-40 min, more preferably 20-30 min; the degradation reaction temperature is preferably 15-40°C, more preferably 20-35°C, more preferably 25-30°C, and the degradation reaction time is preferably 5-35 min, more preferably 10-30 min, more preferably 15-25 min.
[0062] In the present invention, adsorption-desorption equilibrium is achieved after mixing is completed; stirring is performed during the mixing and degradation reaction, and the stirring rate is independently preferably 200-500 r / min, and more preferably 300-400 r / min.
[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0064] Example 1
[0065] Dissolve sodium tungstate dihydrate and sodium silicate in 200mL of deionized water to obtain a mixed solution. In the mixed solution, the concentration of sodium tungstate is 2.75mol / L and the concentration of sodium silicate is 0.4506mol / L; add 130mL of hydrochloric acid (concentration is 6mol / L) to the mixed solution, stir at a rate of 300r / min in a 90℃ water bath for 1h; filter the solution to obtain a filtrate. Add 150mL of sodium carbonate solution (concentration of sodium carbonate is 3.15mol / L) to 300mL of the filtrate, stir at a rate of 300r / min in a 30℃ water bath for 10min to obtain Na 10 [α-SiW9O 34 ]·18H2O precipitation, the precipitate was dried in an oven at 60℃ for 10h, and ground into powder to obtain SiW9.
[0066] Cobalt acetate tetrahydrate was dissolved in 600 mL of deionized water (the concentration of cobalt acetate was 80.03 mol / L); SiW9 was dissolved in 400 mL of deionized water (the concentration of SiW9 was 40.14 mmol / L); the cobalt acetate solution and the SiW9 solution were mixed and stirred at a rate of 300 r / min for 1 h in a water bath at 80°C; the solution was cooled to 30°C and filtered using a cation exchange column; potassium chloride was added to the filtrate (the concentration of potassium chloride in the filtrate was 268.5 mmol / L), and stirred at a rate of 300 r / min for 20 min; the solution was filtered and dried in an oven at 60°C for 10 h, and ground into powder to obtain a dark brown solid [SiW9O 37 {Co(H2O)}3] 10- (SiW9Co3).
[0067] 1.6 g of lithium fluoride and 20 mL of hydrochloric acid (concentration of 9 mol / L) were mixed in a polytetrafluoroethylene reactor and stirred at 300 r / min for 15 min in a 40°C water bath; 1 g of titanium aluminum carbide was added to the reactor and stirred at 300 r / min for 48 h in a 40°C water bath; the reaction solution was centrifuged and washed at a rate of 5000 r / min, first washed twice with 2 mol / L hydrochloric acid, and then washed with deionized water until the pH of the upper liquid was ≥ 6 or the upper liquid turned black; the washed solution was ultrasonicated at a power of 170 W for 1 h in a 20°C ice bath, and then centrifuged at a rate of 3500 r / min for 15 min, the upper liquid was taken, and after dilution, a MXene dispersion with a concentration of 1 mg / L was obtained; the MXene dispersion was refrigerated at 3°C.
[0068] 100 mL of MXene dispersion was mixed with 100 mg of dopamine hydrochloride, and then 80 mg of SiW9Co3 was added to obtain a mixed solution; the pH value of the mixed solution was adjusted to 8.5 with trishydroxymethylaminomethane, and stirred at a rate of 300 r / min in a 25°C water bath for 24 h; the reaction solution was centrifuged and washed twice with deionized water at a rate of 7000 r / min, and the bottom precipitate obtained by centrifugation was dried in an oven at 60°C for 10 h and ground into powder to obtain a MXene-SiW9Co3@PDA composite material.
[0069] The SEM and TEM images of the MXene dispersion prepared in Example 1 are as follows: Figure 1 shown.
[0070] The SEM and TEM images of the MXene-SiW9Co3@PDA composite material prepared in Example 1 are shown in Figure 2 shown.
[0071] The TEM images of the MXene interlayer spacing in the MXene dispersion and MXene-SiW9Co3@PDA composite material prepared in Example 1 are shown in FIG. Figure 3 As shown, a is the TEM image (10 nm) and b is the TEM image (50 nm).
[0072] Example 2
[0073] The preparation method of MXene dispersion is the same as that in Example 1.
[0074] 200 mL of MXene dispersion was mixed with 200 mg of dopamine hydrochloride, and then 200 mg of SiW9Co3 was added to obtain a mixed solution; the pH value of the mixed solution was adjusted to 8.5 with trishydroxymethylaminomethane, and stirred at 300 r / min in a 20°C water bath for 20 h; the reaction solution was centrifuged and washed three times with deionized water at a rate of 7500 r / min, and the bottom precipitate obtained by centrifugation was dried in an oven at 60°C for 11 h and ground into powder to obtain a MXene-SiW9Co3@PDA composite material.
[0075] Example 3
[0076] Dissolve sodium tungstate dihydrate and sodium silicate in 200mL of deionized water to obtain a mixed solution. In the mixed solution, the concentration of sodium tungstate is 2.7mol / L and the concentration of sodium silicate is 0.43mol / L; add 125mL of hydrochloric acid (concentration is 6.2mol / L) to the mixed solution, stir at a rate of 400r / min for 2h in a water bath at 80℃; filter the solution to obtain a filtrate. Add 150mL of sodium carbonate solution (concentration of sodium carbonate is 3.1mol / L) to 270mL of the filtrate, stir at a rate of 400r / min for 15min in a water bath at 25℃ to obtain Na 10 [α-SiW9O 34 ]·18H2O precipitation, the precipitate was dried in an oven at 55°C for 11 h, and ground into powder to obtain SiW9.
[0077] Cobalt acetate tetrahydrate was dissolved in 600 mL of deionized water (the concentration of cobalt acetate was 79 mol / L); SiW9 was dissolved in 400 mL of deionized water (the concentration of SiW9 was 39 mmol / L); the cobalt acetate solution and the SiW9 solution were mixed and stirred at a rate of 400 r / min for 1.5 h in a 70°C water bath; the solution was cooled to 25°C and filtered using a cation exchange column; potassium chloride was added to the filtrate (the concentration of potassium chloride in the filtrate was 200 mmol / L) and stirred at a rate of 400 r / min for 15 min; the solution was filtered and dried in an oven at 55°C for 11 h, and ground into powder to obtain a dark brown solid [SiW9O 37 {Co(H2O)}3] 10- (SiW9Co3).
[0078] 1.2 g of lithium fluoride and 15 mL of hydrochloric acid (concentration of 10 mol / L) were mixed in a polytetrafluoroethylene reactor and stirred at 400 r / min for 10 min in a 35°C water bath; 1.2 g of titanium aluminum carbide was added to the reactor and stirred at 400 r / min for 40 h in a 35°C water bath; the reaction solution was centrifuged and washed at 4000 r / min, first washed 4 times with 1.5 mol / L hydrochloric acid, and then washed with deionized water until the pH of the upper liquid was ≥ 6 or the upper liquid turned black; the washed solution was ultrasonicated at a power of 160 W for 1.5 h in a 10°C ice bath, and then centrifuged at 3000 r / min for 25 min, the upper liquid was taken, and after dilution, a MXene dispersion with a concentration of 1 mg / L was obtained; the MXene dispersion was refrigerated at 3°C.
[0079] 80 mL of MXene dispersion was mixed with 80 mg of dopamine hydrochloride, and then 50 mg of SiW9Co3 was added to obtain a mixed solution; the pH value of the mixed solution was adjusted to 8 with trishydroxymethylaminomethane, and stirred at 400 r / min in a 20°C water bath for 26 h; the reaction solution was centrifuged and washed three times with deionized water at a rate of 6000 r / min, and the bottom precipitate obtained by centrifugation was dried in an oven at 50°C for 11 h and ground into powder to obtain a MXene-SiW9Co3@PDA composite material.
[0080] Example 4
[0081] Dissolve sodium tungstate dihydrate and sodium silicate in 200mL of deionized water to obtain a mixed solution. In the mixed solution, the concentration of sodium tungstate is 2.8mol / L and the concentration of sodium silicate is 0.46mol / L; add 135mL of hydrochloric acid (concentration is 5.8mol / L) to the mixed solution, stir at a rate of 350r / min in a 85℃ water bath for 1.5h; filter the solution to obtain a filtrate. Add 150mL of sodium carbonate solution (concentration of sodium carbonate is 3.2mol / L) to 330mL of the filtrate, stir at a rate of 350r / min in a 35℃ water bath for 20min to obtain Na 10 [α-SiW9O 34 ]·18H2O precipitation, the precipitate was dried in an oven at 70℃ for 9h, and ground into powder to obtain SiW9.
[0082] Cobalt acetate tetrahydrate was dissolved in 600 mL of deionized water (the concentration of cobalt acetate was 81 mol / L); SiW9 was dissolved in 400 mL of deionized water (the concentration of SiW9 was 41 mmol / L); the cobalt acetate solution and the SiW9 solution were mixed and stirred at a rate of 350 r / min for 0.5 h in a water bath at 85°C; the solution was cooled to 35°C and filtered using a cation exchange column; potassium chloride was added to the filtrate (the concentration of potassium chloride in the filtrate was 300 mmol / L), and stirred at a rate of 300 r / min for 25 min; the solution was filtered and dried in an oven at 70°C for 9 h, and ground into powder to obtain a dark brown solid [SiW9O 37 {Co(H2O)}3] 10- (SiW9Co3).
[0083] 2.5 g of lithium fluoride and 30 mL of hydrochloric acid (concentration of 8 mol / L) were mixed in a polytetrafluoroethylene reactor and stirred at 350 r / min in a 45°C water bath for 15 min; 1.5 g of titanium aluminum carbide was added to the reactor and stirred at 350 r / min in a 45°C water bath for 50 h; the reaction solution was centrifuged and washed at a rate of 5500 r / min, first washed three times with 2.5 mol / L hydrochloric acid, and then washed with deionized water until the pH of the upper liquid was ≥6 or the upper liquid turned black; the washed solution was ultrasonicated at a power of 180 W for 0.5 h in a 15°C ice bath, and then centrifuged at a rate of 4500 r / min for 10 min, the upper liquid was taken, and after dilution, a MXene dispersion with a concentration of 1.5 mg / L was obtained; the MXene dispersion was refrigerated at 3°C.
[0084] 130 mL of MXene dispersion was mixed with 130 mg of dopamine hydrochloride, and then 110 mg of SiW9Co3 was added to obtain a mixed solution; the pH value of the mixed solution was adjusted to 9 with tris(hydroxymethylaminomethane), and stirred at a rate of 350 r / min in a 30°C water bath for 20 h; the reaction solution was centrifuged and washed twice with deionized water at a rate of 7500 r / min, and the bottom precipitate obtained by centrifugation was dried in an oven at 70°C for 9 h and ground into powder to obtain a MXene-SiW9Co3@PDA composite material.
[0085] The MXene-SiW9Co3@PDA composite material of Example 1 is used to degrade sulfamethoxazole, norfloxacin, tetracycline hydrochloride, and amoxicillin. The specific method is as follows: the MXene-SiW9Co3@PDA composite material of Example 1 is added to 100mL of antibiotic solution containing 20mg / L sulfamethoxazole, and stirred at a rate of 300r / min for 30min in a 20℃ water bath to reach adsorption-desorption equilibrium; 60mg of peroxymonosulfate (PMS) is added to the reaction solution, and stirred at a rate of 300r / min for 30min in a 20℃ water bath to degrade sulfamethoxazole. Replace sulfamethoxazole with norfloxacin, tetracycline hydrochloride, and amoxicillin, respectively, and the other conditions are the same as the above method, and used to degrade norfloxacin, tetracycline hydrochloride, and amoxicillin.
[0086] The degradation effects of the MXene-SiW9Co3@PDA composite material of Example 1 on sulfamethoxazole, norfloxacin, amoxicillin and tetracycline hydrochloride are as follows: Figure 4 shown.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a polyoxometalate intercalated MXene material, characterized in that: The following steps are included: 1) Sodium tungstate, sodium silicate and water are mixed, the mixed solution is reacted with hydrochloric acid and then filtered to obtain a filtrate; 2) reacting the filtrate with a sodium carbonate solution to obtain a precipitate, and drying the precipitate to obtain SiW9; 3) reacting the cobalt acetate solution and the SiW9 solution, filtering the solution, mixing the filtrate with potassium chloride and drying the mixture to obtain SiW9Co3; 4) performing a first reaction on lithium fluoride and hydrochloric acid, and performing a second reaction on the first reaction product and titanium aluminum carbide to obtain a MXene dispersion; 5) Mixing the MXene dispersion, dopamine hydrochloride and SiW9Co3, adjusting the pH value of the mixture and reacting to obtain a polyoxometalate intercalated MXene material.
2. The preparation method according to claim 1, characterized in that: Step 1) In the mixed solution, the concentration of sodium tungstate is 2.5-3 mol / L, and the concentration of sodium silicate is 0.4-0.5 mol / L; the volume ratio of the mixed solution to hydrochloric acid is 19-21:12-14, and the concentration of hydrochloric acid is 5.5-6.5 mol / L; The reaction temperature is 70-95° C., and the reaction time is 0.5-3 h.
3. The preparation method according to claim 1 or 2, characterized in that: Step 2) the volume ratio of the filtrate to the sodium carbonate solution is 1.5-2.5:1, and the concentration of the sodium carbonate solution is 2.9-3.4 mol / L; The reaction temperature is 20-40° C., and the reaction time is 5-30 min; the drying temperature is 50-80° C., and the drying time is 8-12 h.
4. The preparation method according to claim 3, characterized in that: Step 3) The concentration of the cobalt acetate solution is 78-82 mol / L, the concentration of the SiW9 solution is 38-43 mmol / L, and the volume ratio of the cobalt acetate solution to the SiW9 solution is 2.5-3.5:1.5-2.5; Step 3) The reaction temperature is 60-90°C and the reaction time is 0.5-3h; The concentration of potassium chloride in the mixed solution obtained by mixing the filtrate and potassium chloride is 134.14~ 402.42mmol / L, mixing time is 10 to 30min.
5. The preparation method according to claim 1 or 4, characterized in that: Step 4) The mass volume ratio of lithium fluoride and hydrochloric acid is 0.8-3.6 g:10-40 mL, and the concentration of hydrochloric acid is 6-12 mol / L; the mass ratio of lithium fluoride and titanium aluminum carbide is 0.8-3.6:0.5-2.
6. The preparation method according to claim 5, characterized in that: The concentration of the MXene dispersion is 0.5 to 2 mg / L; the temperature of the first reaction and the second reaction are independently 30 to 45° C., the time of the first reaction is 5 to 20 minutes, and the time of the second reaction is 24 to 60 hours.
7. The preparation method according to claim 1 or 6, characterized in that: Step 5) The volume mass ratio of the MXene dispersion, dopamine hydrochloride and SiW9Co3 is 50-200 mL: 50-200 mg: 5-240 mg; the pH value of the mixed solution is adjusted to 8-9; the reaction temperature is 15-30°C, and the reaction time is 8-30 hours.
8. The polyoxometalate intercalated MXene material prepared by the preparation method according to any one of claims 1 to 7.
9. The use of the polyoxometalate intercalated MXene material according to claim 8 in the degradation of antibiotics, characterized in that: The polyoxometalate intercalated MXene material and the antibiotic solution are mixed, and the mixed solution is subjected to a degradation reaction with peroxymonosulfate.
10. The use according to claim 9, characterized in that: The mass volume ratio of the polyoxometalate intercalated MXene material, the antibiotic solution and the peroxymonosulfate is 10-50 mg: 100 mL: 10-100 mg; The concentration of the antibiotic solution is 10-40 mg / L, and the antibiotic is sulfamethoxazole, norfloxacin, tetracycline hydrochloride or amoxicillin; The mixing temperature is 15-40° C., and the mixing time is 10-40 minutes; the degradation reaction temperature is 15-40° C., and the degradation reaction time is 5-35 minutes.